Methodology of hadith comprehension: interpretation techniques in Fiqh al-Hadith - Ahmad, Arifuddin (Penerbit Universiti Kebangsaan Malaysia, 2016)
An aspect necessary to be developed in Hadith is that of the methods of interpretation. This paper discusses about one methodological aspect of the syarh al-Hadith, namely the interpretation techniques in comprehending Hadith content. The main issue elaborated is 'what are the interpretation techniques in comprehending the content of the Prophet's hadith’. The research is of a development feature implementing philosophical and exegesis approaches. Research findings indicate that in Hadih inquiries aiming to explain its gracious content, there are three interpretation techniques to be applied simultaneously without any dichotomy border disconnnecting them: first, textual interpretation technique, that is interpretation or comprehension of Hadith content based on its text only and/or taking notice of the Hadith narrative technique, language form, style, and content aspects; Second, inter-textual interpretation technique or munasabah hadith, that is interpretation or comprehension of Hadith content focusing on the compatibility of Hadith content, variety of Hadith affair (tanawwu') and/or Hadith function toward the Holy Quran; And third, contextual interpretation technique, that is interpretation or comprehension of Hadith content focusing on the asbab al-Wurud al-Hadis, comprising the Prophet's authority, socio-culture diversity of the Prophet's companions, difference of time, place, affairs of Hadith, and civilization develoment. Implementation of the three techniques will reveal substantive and formalistic senses that in its application (living sunnah) indications of universal, temporal, and local Hadith can be identified.